Evaluating English Oral Production in University Students through Google Meet Using Neutrosophic Z-Numbers - Arihaschna Joyce Berrospi Zapata; Justo Pérez Soncco; Rosita Elvira Alcantara Poma; Lourdes Graciela Lurquin Valdivieso; José Regulo Ramírez Del Águila; Dante Manuel Macazana Fernández (Neutrosophic Sets and Systems)
The present study investigates a central problem in the field of virtual education: how it influences the use of Google Meet in the Oral Production Competition of University Students at a public university in Lima. The research issue focuses on determining whether this platform, widely integrated into current educational environments, effectively contributes to the development of oral communicative skills in a foreign language. In a context where digital technologies are essential for teaching, understanding their real impact is essential to optimize learning processes in non-face-to-face modalities. Therefore, this investigation adopts an innovative approach based on neutral Z numbers, which allows to the analysis of student perceptions with greater depth, including aspects of certainty, uncertainty and denial. The relevance of this issue lies in the growing dependence of higher education institutions of virtual and hybrid environments, as well as the strategic importance of the English domain in a globalized world. However, previous studies on platforms such as Google Meet have tended to privilege traditional quantitative approaches, leaving aside the complexity of students' subjective perceptions. To address this lagoon, semistructured interviews with 40 students were used, evaluated by neutral Z numbers and compared to the UWhitney U test. The results indicate significant differences between those who intensively use the platform and those who do not, highlighting greater confidence in oral production among the former. This research not only enriches the theoretical framework by introducing a novel methodology but also offers practical recommendations to enhance English teaching through digital tools.